2007
DOI: 10.1002/jsfa.2879
|View full text |Cite
|
Sign up to set email alerts
|

The yield and quality of fresh and ensiled plant material from intercropped maize (Zea mays) and beans (Phaseolus vulgaris)

Abstract: An investigation was carried out in the UK to determine whether intercropping with Phaseolus vulgaris beans increases the yield and nutritional quality of maize forage. Fresh and dry yields arising from different sowing dates and different densities of the two species were evaluated, with total nitrogen concentration (TNC) of the plants, and crude protein concentration (CPC), dry matter, metabolizable energy (ME), pH and starch, lactic acid and ash contents of ensiled material. Highest biomass yields of interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 13 publications
7
42
2
2
Order By: Relevance
“…In addition, as long as there is adequate protein available, maize silage has a high starch content and is a useful high-energy feed for cows (e.g. Dawo et al 2007). Silage production has remained fairly stable in most of Europe in recent decades but there has been a shift towards maize silage in some countries (e.g.…”
Section: Exposure To Maize and Wheat Borne Toxins Is Increasingmentioning
confidence: 99%
“…In addition, as long as there is adequate protein available, maize silage has a high starch content and is a useful high-energy feed for cows (e.g. Dawo et al 2007). Silage production has remained fairly stable in most of Europe in recent decades but there has been a shift towards maize silage in some countries (e.g.…”
Section: Exposure To Maize and Wheat Borne Toxins Is Increasingmentioning
confidence: 99%
“…The main purpose of intercropping is to minimize the risk of crop failure and reduce income risks due to unstable market prices for a given commodity. Much research has dealt with the improvement of forage quality through intercropping [10][11][12][13][14][15][16][17][18][19] by investigating the effects of different proportions of leguminous plants. Legume-maize mixtures can be used as a local, protein-rich forage [20], while also having a positive ecological impact by increasing the soil fertility due to the N fixation by rhizobia in symbiosis with legumes [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of that study indicated an increased ratio of soybean in intercrops increased the CP contents. There was a report by Dawo et al (2007) in which CP concentration increased by 22% in the mixture when corn proportion in the mixture decreased by 50%. Results in the present study were in agreement with other studies where legumes also increased CP concentration when in a mixture with corn (Ibrahim et al, 2006;Dawo et al, 2007;Ayub et al, 2008;Dahmardeh et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…There was a report by Dawo et al (2007) in which CP concentration increased by 22% in the mixture when corn proportion in the mixture decreased by 50%. Results in the present study were in agreement with other studies where legumes also increased CP concentration when in a mixture with corn (Ibrahim et al, 2006;Dawo et al, 2007;Ayub et al, 2008;Dahmardeh et al, 2009). Higher forage DM yield with considerable protein content is the ultimate goal of a smallholder farmer when intercropping is practiced (Sadeghpour et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation